CO2 Metallothermal Reduction to Graphene: The Influence of Zn - Luchetta, Carolina; Oliveira Munsignatti, Erica C.; Pastore, Heloise O. (Frontiers in Chemical Engineering, 2021)
CO2 is the most important greenhouse gas involved in climate change; it has been a concern for many years and will remain as such in the years to come. CO2 adsorption and CO2 utilization have been studied as methods to mitigate the concentration of the gas in the atmosphere by sequestering and transforming it into a value-added product, capable of being commercialized. With that aims in mind, CO2 reduction into 3D graphene was studied using a Zn-Mg mixture. The results show that Mg is the only reducing agent, Zn acted as a porogen during graphene formation as the energy released by the reaction between CO2 and Mg is enough to evaporate Zn. Thus, Zn vapor increases graphene porosity and increases the contact of the CO2 with Mg, yielding larger masses of graphene. A relationship between the Zn-Mg ratio and the reaction yield was found.